Nephroprotection by SGLT2i in CKD Patients: May It Be Modulated by Low-Protein Plant-Based Diets? - Cupisti, Adamasco; Giannese, Domenico; Moriconi, Diego; D'Alessandro, Claudia; Torreggiani, Massimo; Piccoli, Giorgina B. (Frontiers in Medicine, 2020)
Sodium-glucose-transporter 2 inhibitors (SGLT2i) are a new class of anti-diabetic drugs that in large trials such as CREDENCE have shown also a reduction of glomerular hyperfiltration and albuminuria in type 2 diabetic patients. Hence, the interest towards SGLT2i is focused towards this potential nephroprotective effect, in order to reduce the progression to overt nephropathy, and it seems to be confirmed in the most recent DAPA-CKD trial. This is the reason why the indication for SGLT2i treatment has been extended to chronic kidney disease (CKD) patients with eGFR up to 30 ml/min, namely with CKD stage 1-3. In patients with CKD stage 3 to 5, the most recent KDIGO guidelines recommend low-protein diet and plant-based regimens to delay end-stage renal disease (ESRD) and improve quality of life. Similarly to SGLT2i, low-protein diets exert renal-protective effects by reducing single nephron hyperfiltration and urinary protein excretion. Beyond the glomerular hemodynamic effects, both protein restriction and SGLT2i are able to restore autophagy and, through these mechanisms, they may exert protective effects on diabetic kidney disease. In this perspective, it is likely that diet may modulate the effect of SGLT2i in CKD patients. Unfortunately, no data are available on the outcomes of the association of SGLT2i and low-protein and/or vegan diets. It is therefore reasonable to investigate whether CKD patients receiving SGLT2i may have further advantages in terms of nephroprotection from the implementation of a low-protein and/or plant-based diet or whether this association does not result in an additive effect, especially in vascular nephropathies.